2013
DOI: 10.2139/ssrn.2284156
|View full text |Cite
|
Sign up to set email alerts
|

Worker or Shirker - Who Evades More Taxes? A Real Effort Experiment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
1
Order By: Relevance
“…Boylan (2010a) found that participants with earned money were more compliant than those benefiting from windfall money before an audit but decreased their compliance after the audit, while the reverse was true for those with endowed money. Other authors found that participants who earn their income through a moderate effort are more likely to comply than those who performed high effort tasks or were exogenously endowed (Bühren & Kundt, 2013;Kirchler et al, 2009). Overall, the available evidence is not conclusive, and we do not have a definite hypothesis on how the origin of income may affect compliance.…”
Section: Media Negativity Bias and Tax Compliancecontrasting
confidence: 63%
See 1 more Smart Citation
“…Boylan (2010a) found that participants with earned money were more compliant than those benefiting from windfall money before an audit but decreased their compliance after the audit, while the reverse was true for those with endowed money. Other authors found that participants who earn their income through a moderate effort are more likely to comply than those who performed high effort tasks or were exogenously endowed (Bühren & Kundt, 2013;Kirchler et al, 2009). Overall, the available evidence is not conclusive, and we do not have a definite hypothesis on how the origin of income may affect compliance.…”
Section: Media Negativity Bias and Tax Compliancecontrasting
confidence: 63%
“…Some studies show that the degree of effort required in experimental tasks could affect compliance behavior (e.g.,Boylan & Sprinkle, 2001;Boylan, 2010b;Durham et al, 2014). Other works find no difference between the behavioral response of subjects who earned their income or were exogenously endowed by experimenters (e.g.,Bühren & Kundt, 2013;Kirchler et al, 2009). AsMalezieux (2018) highlights, the mixed evidence could be caused by interaction effects with other variables like audit probability, tax rate, or gender.…”
mentioning
confidence: 99%
“…The participants received a 5.00 EUR show-up fee and gained on average 3.99 EUR (SD = 0.99 EUR) in an unrelated experiment on tax evasion (Bühren and Kundt, 2013). Our participants were afterwards randomly divided into two subgroups: 80 participants made decisions involving real money (incentivized treatment) and 70 made hypothetical choices (hypothetical treatment) in the Fehr et al (2008) DGs.…”
Section: Methodsmentioning
confidence: 99%